Case Report: Co-infection of tuberculosis and pertussis in a 47-day-old infant and therapeutic strategies - Tang, Qingping; Li, Ruonan; Yang, Xiaotao; Wang, Yanchun; Luo, Yonghan (Frontiers in Pediatrics, 2025)
BackgroundTuberculosis (TB) and pertussis are both highly contagious diseases caused by Mycobacterium tuberculosis (M. tuberculosis) and Bordetella pertussis (B. pertussis), respectively, with significant morbidity and mortality among children. However, neonatal co-infection with these two pathogens is extremely rare, and no such cases have been reported in the literature to date.Case presentationWe reported a case of a 47-day-old full-term male infant admitted with cough and fever. Chest imaging revealed bilateral pulmonary consolidation. Bronchoalveolar lavage confirmed co-infection with M. tuberculosis and B. pertussis. Initial empirical antibiotic therapy was ineffective. Based on pathogen identification, treatment was adjusted to a combination of levofloxacin, isoniazid, rifampicin, and pyrazinamide. During treatment, the infant developed drug-induced liver injury, prompting several modifications to the anti-TB regimen, including the introduction of linezolid and adjunctive corticosteroids. With individualized therapeutic adjustments and close liver function monitoring, the infant's condition improved significantly, and he was eventually discharged in stable condition.ConclusionThis case underscores the importance of considering atypical pathogens in neonates presenting with severe unexplained pneumonia, particularly in regions endemic for TB and pertussis. Tailored antimicrobial strategies and dynamic assessment of drug toxicity, especially hepatotoxicity, are essential for successful management.